DEVELOPMENT OF THE WORLD VIEW OF LIFE ACTIVITY SAFETY IN PRIMARY CLASS STUDENTS - Ismoiljon Rakhmanov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
As a result of changes in the world, the safety of life activities is becoming one of the important concepts. It is necessary to constantly expand the ideas of students about safety in the world in the development of the world view of the safety of life activities of primary school students. Developing a worldview can be developed as a result of acquiring knowledge and skills to deal with and eliminate various risks and emergency situations.